2003
DOI: 10.1128/jvi.77.3.2174-2181.2003
|View full text |Cite
|
Sign up to set email alerts
|

Virus Replication in Engineered Human Cells That Do Not Respond to Interferons

Abstract: The V protein of the paramyxovirus simian virus 5 blocks interferon (IFN) signaling by targeting STAT1 for proteasome-mediated degradation. Here we report on the isolation of human cell lines that express the V protein and can no longer respond to IFN. A variety of viruses, particularly slow-growing wild-type viruses and vaccine candidate viruses (which are attenuated due to mutations that affect virus replication, virus spread, or ability to circumvent the IFN response), form bigger plaques and grow to titers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 23 publications
(20 reference statements)
5
81
0
1
Order By: Relevance
“…Consistent with this, many wild-type viruses form bigger plaques on cells engineered to be non-responsive to IFN than on the parental cells (Young et al, 2003). Consequently, until viruses can synthesize enough of the viral IFN antagonist(s) to limit the IFN response, it is also important for viruses to keep production of any potential inducer(s) of IFN to a minimum.…”
Section: General Considerations Of How Viruses Evade the Ifn Responsementioning
confidence: 76%
See 3 more Smart Citations
“…Consistent with this, many wild-type viruses form bigger plaques on cells engineered to be non-responsive to IFN than on the parental cells (Young et al, 2003). Consequently, until viruses can synthesize enough of the viral IFN antagonist(s) to limit the IFN response, it is also important for viruses to keep production of any potential inducer(s) of IFN to a minimum.…”
Section: General Considerations Of How Viruses Evade the Ifn Responsementioning
confidence: 76%
“…For example, the NSs protein of Bunyamwera virus (BUNV) inhibits cellular mRNA transcription by blocking the activity of RNA polymerase II (Thomas et al, 2004). However, a recombinant BUNV that does not encode a NSs protein is pathogenic in IFN-a/b receptor-knockout mice and grows to high titres in cells that do not produce IFN (Weber et al, 2002;Young et al, 2003). Similarly, the NSs protein of La Crosse virus (LACV) serves primarily to suppress the IFN response of mammalian hosts (Blakqori et al, 2007).…”
Section: General Considerations Of How Viruses Evade the Ifn Responsementioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that the efficiency with which a given virus overcomes the IFN response may be extremely important for its pathogenesis and host range (34,35). Strategies used by virus-encoded IFN antagonists include general inhibition of cellular gene expression, sequestration of molecules in the IFN-induction pathway, and cleavage or degradation of innate immune components (reviewed in Refs.…”
mentioning
confidence: 99%